Never laugh as a hearse goes by - Duncan, Elizabeth J. (Duncan, Elizabeth J. Penny Brannigan mystery., 2013)
"Spa owner and habitual amateur sleuth Penny Brannigan finds herself at a clerical conference at Gladstone's Library in North Wales. Also attending as a guest speaker is her boyfriend, DCI Gareth Davies, there to give a talk on theft prevention. But behind the ornate red sandstone fac̦ade of this most respectable of Victorian buildings, Penny encounters deception, marital and financial infidelity, a sham marriage scam, blackmail for beginners, and someone bent on murder. When the bishop's secretary dies of a suspicious case of food poisoning, Davies leads the investigation. At Penny's suggestion, Florence Semble, a friend from Penny's adopted hometown, is invited to the Library to decode the secretary's shorthand notebook in the search for clues. As the conference continues, another body is found in the beautiful library itself, and Penny must once again search for a killer. Never Laugh As a Hearse Goes By is a fine entry in a series celebrated for its small town charm, Welsh flavor, and loveable characters"--